Potensi Senyawa Antibakteri dari Ekstrak Akar Manis (Glycyrrhiza glabra L) terhadap Bacillus cereus - Gandi Sogandi; Wan Syurya Tri Darma; Raudatul Jannah (Jurnal Kimia Sains dan Aplikasi, 2019)
The high number of poisoning food and diarrheal diseases caused by Bacillus cereus bacteria has been treated with chemical drugs and traditionally herbal plants. One of the commonly used herbal plants is sweet root (Glycyrrhiza glabra L.). This study aims to extract and fractionate sweet root plants, determine the antibacterial activity and identify the types of bioactive compounds as antibacterial compounds. The extraction process uses a maceration technique and fractionation using buthanol, ethyl acetate, and hexan solvents. Antibacterial activity was carry out by the diffusion method and identification of bioactive compounds by GCMS analysis. This study showed that greatest antibacterial activity was found in ethyl acetate fraction with a strong category and MIC value of 12,5%. This study for the first time also revealed that the types of bioactive compounds from sweet root plants (Glycyrrhiza glabra L.) as antibacterial compounds are n-Hexadecanoic as a fatty acid group and 4H-Pyran 4-one 2.3 dihydro-3, 5-dihydroxy-6 methyl from the flavonoid group.